The Role of Community Health Centers in Early Detection and Initial Management of Cardiovascular Emergencies - Br Bangun, Callina Floriana Yudisia (JURNAL KEBIDANAN KESTRA (JKK), 2024)
Cardiovascular emergencies (CED) are medical conditions that require rapid treatment to prevent death or disability. Community Health Centers (CHCs), as first-level health care facilities, play an essential role in the early detection and early management of CED. This study aims to evaluate the role of CHCs in the early detection and management of CED in the research area. It also seeks to examine the relationship between demographic factors and the success of CED management at CHCs. The research used a quantitative approach with an analytical observational design. Data were collected through both primary and secondary sources from local CHCs. Univariate analysis was performed to assess the frequency distribution of the relevant variables, while bivariate analysis employed the chi-square statistical test to examine the relationship between demographic factors (such as age, gender, nutritional status) and the success of cardiovascular emergency management. The univariate analysis results indicated that the majority of patients experiencing CED were between the ages of 45-60, with chest pain as the primary complaint. The CHCs have implemented early detection activities using an electrocardiogram (ECG) device; however, there are challenges related to limitations in human resources and facilities. Bivariate analysis revealed a significant relationship between age and gender with the success of early CED management, with better outcomes observed in patients who received prompt treatment. Other influencing factors include the level of education and public awareness of the importance of regular check-ups.